Strategi Pembinaan Karakter Religius Peserta Didik dalam Program Asrama Madrasah Negeri - Dewi Faizatul Isma; Fara Priyan Fauzia; Aulya Zahrotin Maghfiroh; Zkiya Sayidatun Nisa; Yusriah Nabil Latifah; Ardiansyah Mustofa (WISE Pendidikan Indonesia, 2025)
Religious character development is a crucial issue in Islamic education, particularly amid the growing challenges of moral degradation, weak worship discipline, and the influence of digital culture on students’ behavior. This study aims to analyze the strategies for fostering students’ religious character through the boarding school program at Ma’had Kyai Ageng Hasan Besari, MTsN 1 Ponorogo, as well as to identify its implications, supporting factors, and inhibiting factors. This research employed a qualitative case study approach. Data were collected through observation, semi-structured interviews, and documentation involving boarding school caregivers, teachers, musyrif or musyrifah, and students. The data were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing, while data validity was strengthened through source and technique triangulation. The findings indicate that religious character development was implemented through three main strategies: worship habituation, guidance and advice, and religious environmental conditioning. These strategies were realized through structured programs such as congregational prayer, Qur’an recitation and memorization, evening diniyah classes, muhadharah, KOSERI, and daily discipline formation in the boarding environment. The program had positive implications for students’ worship discipline, responsibility, independence, obedience to rules, and social morality. The success of the program was supported by family involvement, active caregivers, positive peer interaction, and students’ personal commitment, while the main obstacles included uncontrolled mobile phone use, overlapping school and boarding schedules, and students’ adaptation difficulties. The study implies that boarding school programs in state madrasahs can serve as an effective religious character education ecosystem when supported by systematic habituation, exemplary guidance, consistent supervision, and stronger coordination between schools, boarding managers, and families.